A comparative study of small mammal diversity of oil palm plantation and nearby forest / Muhammad Rasul bin Abdullah Halim - Abdullah Halim, Muhammad Rasul (2014)
Large areas of tropical forests around the world were critically converted into agricultural areas especially oil palm plantation and for other human activities. Malaysia is one of the leaders in oil palm production and conversion of natural ecosystems into agricultural area gives an impact to the local biodiversity. This study aims to compare the diversity and abundance of small mammal species in two different habitats; forested habitat and oil palm plantation in Pahang, Malaysia. The study also intends to investigate the effects of forest edge distances (i.e. adjacent, intermediate, and interior forests) and various ages of oil palm plantation (i.e. young, mature, and old) on small mammal communities. Mist-netting, harp-trapping and cage trapping techniques were applied in all study areas from March 2010 until June 2012. A total of 1125 individuals of non-volant small mammals belonging to 22 species and 4 families were captured. The species richness and diversity of non-volant small mammals were significantly higher in the forested habitat than in oil palm plantation but no significant difference for oil palm ages. Species richness of non-volant small mammals was higher in the adjacent forest than intermediate and interior forests. Malayan Wood Rat (Rattus tiomanicus) dominated oil palm plantation habitat while Bowers’s Rat (Berylmys bowersi) was only found in the intermediate forest. Meanwhile, a total of 526 individuals of volant small mammals belonging to 36 species and 5 families were captured which revealed significant higher number in the forest habitat contrast to the oil palm plantation. There were predominated by common species such as Horsfield’s Fruit Bat (Cynopterus horsfieldi) and Short-nosed Fruit Bat (Cynopterus brachyotis) in the oil palm plantation. This study concluded that habitat types are important in determining the occurrences and composition of small mammals. A complex vegetation structure such as forested areas provided increased microhabitat and availability of food resources compared to oil palm plantation. Thus, proposed in order to promote biodiversity within oil palm landscape the biodiversity outcomes to retain remaining patches of forest within and around the oil palm plantation. The work would assist efforts for conservation strategies and ensuring sustainable management of plantations.